SEMIOTIC ANALYSIS ON THE CONCEPT OF LOVE IN NIZAR QOBBANI’S RISALAH MIN TAḤT AL-MĀ'I - Fikri, Maulana Muhammad; Al Anshory, Abdul Muntaqim; Ramdhani, Mikail Muhammad (Annual International Conferences on Language, Literature, and Media; Vol 4 (2022): The 4th Annual International Conference on Language, Literature and Media, 2022)
The language of poetry often uses distinctive languages ​​and contains many signs. This requires special studies, including semiotic studies. This study aims to analyze the Arabic poetry Risalah Min Taht Al-Ma'i by Nizar Qobbani based on Michael Riffaterre's semiotic perspective, which includes heuristics & hermeneutics, indirectness of expression, matrix, model, variant, and hypogram. This research is qualitative with the main data in the form of the arabic poetry Risalah Min Taht Al-Ma'i by Nizar Qobbani. Data collection techniques used are reading and note-taking techniques. The data analysis technique is in the form of qualitative data analysis techniques, which consist of data reduction, data presentation, and drawing conclusions. The results showed that the arabic poetry Risalah Min Taht Al-Ma'i by Nizar Qobbani talks about love as a force that has a big influence on life, realized from various aspects of human emotions. This data is contained in heuristic and hermeneutic processes, indirect expressions that use language styles such as metaphors and personifications, divided into matrixes, models & variants, and motivated by a hypogram that is in accordance with the concept of love